The Effect of Motivation and Communication on Employee Performance with Employee Engagement as an Intervening Variable in The PT XYZ Contact Center - Ramdhani, Reza Fitrah; Djamil, Masydzulhak (Dinasti Publisher, 2024)
This study aims to determine the effect of Motivation and Communication on Employee Performance with Employee Engagement as an intervening variable at the PT XYZ Contact Center. The number of samples in this study was 103 people who were determined by the saturated sampling technique. This study uses quantitative methods and statistical analysis of Structural Equation Modeling and Partial Least Square (SEM-PLS) 3.3.9 software. The results of this study indicate that motivation has a positive and significant effect on employee engagement and employee performance. Communication has no significant effect on employee engagement and employee performance. Employee engagement has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance through employee engagement. And communication has no significant effect on employee performance through employee engagement.